Analysis of Factors Affecting Patient Loyalty in Bandung General Hospital in Medan - Irma Susanti; Mappeaty Nyorong; Sudiro Sudiro (Journal La Medihealtico, 2020)
Patient loyalty greatly affects the survival of a hospital, because loyal patients not only make repeated visits but can act as loyalty advocators. In the last five years, there has been a decrease in the number of inpatient visits at RSU (Regional General Hospital) Bandung Medan, an average of 8.79% so that research is needed to determine the factors that affect patient loyalty. The study was conducted by cross sectional, using a questionnaire that has been tested valid and reliable. The research variables were service quality, patient satisfaction, and patient loyalty. The number of samples was 100 patients who met the criteria. Data were analyzed using SEM-PLS method. The results: service quality has a significant effect on patient satisfaction, patient satisfaction has a significant effect on patient loyalty, and service quality has a significant effect on patient loyalty. Patient loyalty at RSU Bandung Medan is significantly influenced by service quality factors and patient satisfaction factors. Regarding the service quality variable, 20% of respondents did not agree that nurses recorded accurately. In the patient satisfaction variable, 20% of respondents were dissatisfied with the cleanliness of the room, 20% of respondents were not satisfied with the food served, and 15% of respondents were dissatisfied with the results of the treatment. In the patient loyalty variable, 15% of respondents disagreed with giving positive responses to the relationship about the performance of the Bandung Hospital, and 15% of respondents would move to another hospital if they got a discount.